Effects of Aging and Sarcopenic Obesity Type on Metabolic Syndrome Risk Factors in Elderly Women - InHwa Yoo; Mihyun No; Hyoun-Joong Kong; Jeeyoung Hong (Asian Society of Kinesiology, 2018)
PURPOSE The purpose of this study was to examine whether there was any difference between metabolic syndrome risk factors following aging and sarcopenic obesity types in elderly women. METHODS A random sampling of 224 women older than 65, who had completed health screening at health centers located in K-gu and S-gu, was used to conduct this study. All participants had gone through dual-energy x-ray absorptiometry (DEXA) and a metabolic syndrome risk factor test. In order to examine the effects of aging on metabolic syndrome risk factors, the study divided the subjects into three groups based on age: 60s (66.91±1.33, n=62), 70s (75.16±2.25, n = 87), and 80s (85.08±3.26, n=75). In order to examine the effects of sarcopenic obesity type on metabolic syndrome risk factors, we divided the subjects into four groups: normal weight group (n=34), sarcopenia group (n=8), sarcopenic obesity group (n=89), and obesity group (n=93). To compare these groups, securing regularity in all evaluation variables, we conducted a one-way ANOVA and used the LSD (least significant difference) test for a post hoc analysis with statistical significance set at α= .05. RESULTS The 60s group had greater upper limb mass, lower limb mass, and appendicular skeletal muscle mass than the 70s group and the 80s group. The 60s and 70s groups had higher HDL cholesterol than the 80s group, while the 60s group had lower triglycerides than the 70s and 80s groups. The 60s and 70s groups had higher diastolic blood pressure than the 80s group. The normal weight group had lower waist circumference than the other three groups and the sarcopenic obesity group had higher waist circumference than the obesity group. The normal weight group had higher HDL cholesterol than both the sarcopenia group and the sarcopenic obesity group, whereas the sarcopenia group had lower HDL cholesterol than the obesity group. The obesity group had higher diastolic blood pressure than the normal weight group and the sarcopenic obesity group. CONCLUSIONS In conclusion, the 60s group had more muscle mass than the 70s group and the 80s group and the least metabolic syndrome risk factors. Elderly people with normal weight did not have sarcopenia and obesity, and also showed the least metabolic syndrome risk factors. This study suggests that diverse methods must be sought for the elderly to maintain normal weight not accompanied by sarcopenia and obesity.